Faktor Ekonomi Sebagai Alasan Perceraian - Muhammad Habib (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
The background of this research is that based on the identification that the researchers did at the research location, it was the economic factor that was the most common cause of divorce in the household. In this case divorce is meant because economic factors are a matter of family livelihood, among them there are husbands who are not responsible for the needs of their families and do not work hard to fulfill their obligations, and there are also among husbands who are actually responsible and keep trying to provide a living, however his wife had a luxurious lifestyle so he demanded a living that her husband could not fulfill and then filed for divorce. The objectives of this research are: First, to find out the meaning of divorce. Second, to find out whether economic factors must be examined as a cause of divorce.Third, to find examples of divorce cases because of economic factors. This type of research is the process and meaning in the perspective of the subject more highlighted in qualitative research. With the results of the study: Showing that the divorce rate in the Langkat District Religious Court continues to increase. As for divorce due to economic factors is the most factor in causing divorce in the Langkat District Religious Court in 2019 as many as 1458 cases or around 80.87% of the total divorces that occurred in 2019 while the remaining 19.13% was the 12th percentage factor causes of divorce other than economic factors. Keywords: Divorce, Economic, Factors.